Monochrome memories: nostalgia and style in 1990s America - Grainge, Paul (2000)
Memory is central to the way that cultures produce, negotiate and contest ideas of nationhood. This work examines how, as an aesthetic mode of nostalgia, the black and white image was used in the 1990s to establish and legitimate particular kinds of memory within American cultural life. It locates the production of visual (monochrome) memory in different forms of cultural media and explores how attempts were made in the nineties to authorize a consensual past, a core memory - what might be called an archival essence - for a stable and unified concept of "America." The 1990s were a period when liberal ideologies of nationhood and mythologies of Americanness came under particular, and intensified, pressure. In a time when national identity was being undermined by transnational political and economic restructuring, when ideas of national commonality were being challenged by an emergent politics of difference, and when the metanarratives of memory were straining for legitimacy against the multiple pasts of the marginalized, the desire to stabilize the configuration and perceived transmission of American cultural identity became a defining aspect of hegemonic memory politics. By considering monochrome memory in nineties mass media, I look at the way that a particular "nostalgia mode" was used stylistically within visual culture and was taken up within a discourse of stable nationhood.